Why do they want to become English teachers: a case study of Taiwanese EFL teachers - Shih, Chih-Min (Faculty of Education, University of the Free State, 2016)
Although it has been argued that knowledge on initial motivation for choosing teaching as a career is necessary for improving teacher education programmes and teacher education policies, there is a lack of research investigating this issue in the fields of English as a second language (ESL) and English as a foreign language (EFL). Grounded in Watt and Richardson’s (2007) Factors Influencing Teaching Choice (FIT Choice) framework, which laid its foundation on expectancy-value theory, this study fills that research gap by examining why EFL teachers chose teaching as a career. Thirty-eight EFL teachers with diverse backgrounds were interviewed. The results indicated that the participants became EFL teachers mainly for complicated, multi-layered reasons. They were attracted to teaching because of its intrinsic career value and its salary. The former refers to the fact that they enjoyed English or that they wanted to become a teacher since childhood. The latter applied to those who were either pleased with the salary or who could strike a balance between work and life, work and study or work and health while earning a competitive salary. Surprisingly, the participants rarely mentioned personal utility value (e.g., job security) as motivation. This study suggests that ESL/EFL teachers require intrinsic and extrinsic motivations to commit to teaching.
Keywords: EFL teacher; Initial motivation for teaching; Taiwan; Career; Factors influencing Teaching Choice framework